Carbon Monoxide Interacts with Auxin and Nitric Oxide to Cope with Iron Deficiency in Arabidopsis - Yang, Liming; Ji, Jianhui; Wang, Hongliang; Harris-Shultz, Karen R.; Abd_Allah, Elsayed F.; Luo, Yuming; Guan, Yanlong; Hu, Xiangyang (Frontiers in Plant Science, 2016)
Carbon monoxide (CO) and nitric oxide (NO) are essential modulators that regulate the plant response to iron deficiency (-Fe). Auxin is a phytohormone that plays important roles in plant growth and development. We report here that in Arabidopsis –Fe enhanced heme oxygenase-dependent CO generation and auxin transport through redistribution of PIN1 protein, which subsequently increased NO accumulation; NO signaling regulated the activity of ferric chelate reductase (FCR) and the expression of Fe-uptake genes including basic helix-loop-helix transcription factor (FIT) and the ferric reduction oxidase 2 (FRO2). Over-expression of HY1 encoding heme oxygenase, or treatment with CO donor enhanced basipetal auxin transport, FCR activity, and the expressions of FIT and FRO2 under –Fe. Such effects were compromised in the mutant aux1-7 impaired in auxin transport or in the mutant noa1 or nia1/nia2 defective in NO biosynthesis. -Fe failed to promote auxin transport and FCR activity in hy1 mutant; such inability was reversed in the double mutant of hy1/yucca1 with elevated auxin production, or in hy1/cue1 mutant with NO over-accumulation. Taken together, our results suggest that CO modulates NO signaling through auxin to cope with Fe deficiency in Arabidopsis.